A Humean Argument for the Land Ethic?. (1st November 2001) - Lo, Y.S.
Abstract : This article examines an allegedly Humean solution provided by J. Baird Callicott to the problem of the is/ought dichotomy. It also examines an allegedly Humean argument provided by him for the land ethic's summary moral precept. It concludes that neither the solution nor the argument is Humean or cogent.